Exotic preferences - Loewenstein, George (Oxford University Press, 2007)
This book brings together a selection of his papers focusing on what he calls "exotic preferences"--the disparate motives that drive human behavior. In addition to covering the history and methodology of behavioral economics, they also touch on a wide range of fascinating topics such as the motives that drive extreme athletes, our propensity to want to get unpleasant experiences out of the way so we can focus on the more pleasant, and the psychology of curiosity. There are also papers on social preferences, discussing the importance of perceptions of fairness in interpersonal interactions, intertemporal choice--the tradeoffs between costs and benefits occurring at different points in time--and the impact of emotion on economic decision making. An original introduction outlines Loewenstein's general approach to research, and there are short introductions to each paper outlining briefly when, how and why they came to be written, providing a fascinating and vivid insight into the process of intellectual creativity